Building and Codifying the Test of Defensive Moves and Shooting Accuracy from Jumping in Front for Handball Players Ages (15-17) Years - Mustafa Essa Eqab; Hamid Saleh Mahdi (Indian Journal of Forensic Medicine & Toxicology, 2021)
The importance of the research lies in the construction and codification of a test for defensive moves and theshooting accuracy from front jumping for handball players and placing this test under the hands of coaches todetect the levels of handball players of ages (15-17 years), and work to develop their levels through this test.And to achieve the goals, the researchers used the descriptive method in the survey method to suit it with theresearch problem, and the research community included handball players of (15-17 years), and the samplewas chosen by the deliberate method, and their number is (60) players, which represent a percentage of(57.14%) of the research community, the researchers conducted exploratory experiments. The validity of thetest was confirmed and its scientific characteristics (truthfulness, consistency, and objectivity) were verifiedas well as its ability to distinguish the research sample, and appropriate statistical treatments were carriedout. The process of evaluating the game of handball, and contributes to raising the levels of skills (defensiveand offensive) handball research subject, the researchers recommend the adoption of the defensive movestest and the accuracy of shooting by jumping forward in the process of continuous evaluation of the playersin addition to this is an important factor in selecting qualified players within their clubs and the national teamwith handball, and building other complex tests on age groups other than the current research sample as wellas complex skills (defensive and offensive) that were not discussed, as well as the interest in training theskills that were covered in the study and comprehensive scientific approaches to the complex skill aspects(defensive and offensive) together.